C4d, a high-affinity LilrB2 ligand, is elevated in Alzheimer’s disease and mediates synapse pruning - Barbara K. Brott; Aram J. Raissi; Kristina D. Micheva; Jost Vielmetter; Monique S. Mendes; Caroline J. Baccus; Jolie Huang; Carla J. Shatz (Proceedings of the National Academy of Sciences, 2025)
Synapse pruning sculpts neural circuits throughout life. The human Leukocyte immunoglobulin-like receptor type B2 (LilrB2)/murine Paired immunoglobulin receptor B (PirB) receptors expressed in neurons and complement protein C4 have been separately implicated in pruning. Here, we report that C4d, a C4 cleavage product with unknown function, binds LilrB2/PirB with nanomolar affinity. C4d and LilrB2 colocalize at excitatory synapses in the human cerebral cortex as well as with beta amyloid in Alzheimer’s disease (AD). C4d, as well as C4, increase with age and more so in AD. To examine whether C4d-PirB interactions can drive pruning, dendritic spines—the postsynaptic structure of excitatory synapses—were monitored on L5 pyramidal neurons in the mouse cerebral cortex: A significant decrease in dendritic spine density occurred in WT with C4d exposure, but KO of PirB completely prevented this loss. Together, our findings reveal an unexpected physiological role for C4d in pruning and imply that different complement cascade components may collaborate to engage both neuronal and glial-specific effectors of synaptic pruning.